Desain Arsitektur Interior Preschool yang Fun, Playful dan Edukatif - Tryphena, Angelia; Purwoko, Gervasius Herry; Prihatmanti, Rani (Universitas Ciputra Surabaya, 2015)
Every parent certainly wants the best for their children. Childhood is the period where children experience growth and development in many aspects; physically, intellectually, socially, and emotionally. However, it seems that nowadays many parents are not capable to fully attend their children’s needs because of job demands. That is why many start to entrust their children’s first formal education to preschool. Preschool can stimulate the growth and development of the children by letting them learn and play. The learning process can accelerate well if the preschool has qualified teachers, good program, and proper physical environment. The children will feel uncomfortable to learn and play in dark, humid, and overcrowded place. Therefore, classrooms and other facility rooms need to be designed as comfortable as possible to support children’s need and growth in the learning process. Selection of colors, shapes, furniture and room layout should be done properly in accordance with children’s ergonomics, and should pay attention to the safety for its users.Interior architecture design Town for Kids Preschool with Playful Kid’s Town as a theme is to provide a comfortable preschool for children to maximize learning process through visual, audio and kinesthetic. Theme is applicable in selection of primary colors to enhance the spirit of children’s activities, simple geometric shapes according to the level of children’s learning abilities and playful design as children’s learning media.